PENGARUH KEMAJUAN TEKNOLOGI INFORMASI BAGI ANAK USIA DINI: BAGAIMANA PENDAMPINGAN ORANGTUA DALAM MENGHADAPI TANTANGAN KEMAJUAN TEKNOLOGI BAGI ANAK - Priyanti Lubis, Dian Rizky; Haulika, Teguh Iman; Kayla, Zahwa; Satria, Andy (Psikologi Prima, 2023)
Technology is developing rapidly, widely, and rapidly. This causes various influences on human life patterns, both patterns of thought and behavior. As we know, smartphones in this era have a very rapid development. All groups of adults, students, and children use them. Parents need to be more understanding of using and utilizing information technology to help children's growth and development, and the strong influence of information technology in people's lives raises concerns for some parents that this technological progress will only hurt children's growth and development. Some parents use smartphones as a shortcut in assisting children, and parents use them to accompany their children so that they can carry out activities without worrying about their children playing dirty and messing up the house, which will make them cranky and disturb their parents. Parents should pay more attention to supervising and monitoring what children do when using smartphones to reduce the negative impact caused by the use of smartphones, which should be used and utilized for positive things. Early childhooders tend to be happy with the new things they get through play activities; playing is enjoyable for children, allowing them to explore all potential. Parents giving smartphones in early childhood will undoubtedly affect the development of children. Smartphones should not be given in early childhood because, at that age, children should be taught to get to know the environment and socialize well.